2017
DOI: 10.1051/0004-6361/201629639
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cosmic web filaments on the properties of groups and their central galaxies

Abstract: Context. The nature versus nurture scenario in galaxy and group evolution is a long-standing problem not yet fully understood on cosmological scales. Aims. We study the properties of groups and their central galaxies in different large-scale environments defined by the luminosity density field and the cosmic web filaments. Methods. We use the luminosity density field constructed using 8 h −1 Mpc smoothing to characterize the large-scale environments. We use the Bisous model to extract the filamentary structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 85 publications
9
54
1
Order By: Relevance
“…Kuutma et al (2017) find that at fixed density, high-mass galaxies (M r < −20 mag) within filaments have reduced star formation rates (but not higher masses) and are more likely to have early-type morphologies. Poudel et al (2017) find that at fixed group mass and environmental density, groups in filaments are more luminous, and central galaxies in filaments have redder colors, higher masses, and lower specific star formation rates.…”
Section: Introductionmentioning
confidence: 81%
“…Kuutma et al (2017) find that at fixed density, high-mass galaxies (M r < −20 mag) within filaments have reduced star formation rates (but not higher masses) and are more likely to have early-type morphologies. Poudel et al (2017) find that at fixed group mass and environmental density, groups in filaments are more luminous, and central galaxies in filaments have redder colors, higher masses, and lower specific star formation rates.…”
Section: Introductionmentioning
confidence: 81%
“…In filaments, several observational studies (Codis et al 2012;Tempel et al , 2015Tempel & Libeskind 2013;Hirv et al 2017) indicate that the major axes (perpendicular to spin axes) of early-type galaxies are expected to be aligned with the direction of the host filaments because major mergers that form early-type galaxies occur along the filament, making their major axes parallel to the directions of the filaments. Furthermore, in filaments, central galaxies in groups tend to be early-type galaxies compared with galaxies outside of the filaments (e.g., Kuutma et al 2017;Poudel et al 2017). This suggests that the filament environment could efficiently transform the galaxy morphology from late-to early-type.…”
Section: Discussionmentioning
confidence: 99%
“…They worked in a probabilistic Bayesian framework and adopted a filament radius of 0.5h −1 Mpc. Previous work using these catalogs has shown that being inside a filament affects galaxy properties even when comparing with non-filament galaxies at fixed local (aperture) density (Poudel et al 2017). When determining the distance to the nearest filament for each member of our HUDs samples, we first limit our calculations to those that are fully enclosed by the volume of the Tempel et al (2014) catalog.…”
Section: Distance From Nearest Filamentmentioning
confidence: 99%